2020
DOI: 10.11648/j.ijla.20200804.20
|View full text |Cite
|
Sign up to set email alerts
|

Implicature and Deixis of Novel Laskar Pelangi and Novel Mimpi-Mimpi Lintang by Andrea Hirata

Abstract: The purpose of this study are; (1) Describe the implicatures contained in the Laskar Pelangi novel and the dreams of Lintang Maryamah Karpov by Andrea Hirata, (2) Describe deixis contained in the Laskar Pelangi novel and the dreams of Lintang Maryamah Karpov by Andrea Hirata. This research includes qualitative descriptive research. The focus of this research is identifying; (1) variety and form of implicature (2) variety of deixis. Data collection uses marking reading techniques and note taking techniques. Dat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…An investigation carried out within a novel revealed the existence of non-conventional implicatures and conventional implicatures, as well as presupposition implicatures. There are four ways to express the implicatures: phrase statements, command sentences, enquiry sentences, and exclamation sentences (Azis, Thaba, and Rukayah 2020). In another study, two different types of implicatures were found, with the maxim of relation being the one that was observed the most frequently (Yulianti et al 2022).…”
Section: Introductionmentioning
confidence: 99%
“…An investigation carried out within a novel revealed the existence of non-conventional implicatures and conventional implicatures, as well as presupposition implicatures. There are four ways to express the implicatures: phrase statements, command sentences, enquiry sentences, and exclamation sentences (Azis, Thaba, and Rukayah 2020). In another study, two different types of implicatures were found, with the maxim of relation being the one that was observed the most frequently (Yulianti et al 2022).…”
Section: Introductionmentioning
confidence: 99%